Peningkatan Daya Imun dengan Pemberian Temu Mangga (Curcuma mangga Val.) pada Tikus Wistar Jantan: Immune System Increasing Through Orally Temu Mangga (Curcuma mangga Val.) Intake on Male Wistar Rats - Pujimulyani, Dwiyati; Yulianto, Wisnu Adi; Windrayani, Emi; Windrayahya, Sulkhan (Faculty of Agricultural Technology, University of Jember, 2025)
Temu mangga (Curcuma mangga Val.) can enhance immune function due to its active compounds. The purpose of this study was to determine the antioxidants level and total phenol content of blanch-treated Curcuma mangga powder, then evaluate immunological enhancement through orally Curcuma mangga Val. intake on Wistar male rats (in-vivo). Temu mangga rhizomes were peeled, washed, and subjected to steam blanching for varying times (0, 2.5, 5, 7.5, and 10 minutes). Blanch-treated temu mangga was dried using a cabinet dryer, ground, and sieved to obtain powder. Analysis of the temu mangga powder included antioxidant activity (DPPH) and total phenol content. In-vivo testing on experimental rats included SOD, IgE, IgG, and IgM levels. The selected temu mangga rhizome, steam-blanched for 5 minutes, exhibited excellent antioxidant properties (81.46% RSA DPPH value and 6.08 mg GAE/g total phenol content). According to the in vivo results, the group of rats receiving temu mangga showed a notable increase in SOD levels (72.92%) compared with the NaCMC-treated group, and were not substantially different from commercially available supplements (stimuno). Experimental rat antibody values were IgE at 74.02 ng/mL, IgG at 18.20 ng/mL, and IgM at 2.97 ng/mL, significantly better in rats given temu mangga powder than those given Na-CMC and stimuno. In the future, this study can provide more insight into the potential of Curcuma mangga Val. processed by steam blanching and its potential as an immunomodulator. Keywords: antioxidant activity, blanching, immunomodulator, in-vivo, temu mangga